Concatenation of convolutional codes and rank metric codes for multi-shot network coding - Napp, Diego (2018)
In this paper we present a novel coding approach to deal with the transmission of information over a network. In particular we make use of the network several times (multishot)and impose correlation in the information symbols over time. We propose to encode the information via an inner and an outer code, namely, a Hamming metric convolutional code as an outer code and a rank metric code as an inner code. We show how this simple concatenation scheme can exploit the potential of both codes to produce a code that can correct a large number of error patterns.